Relationship Types and Contraceptive Use Within Young Adult Dating Relationships. Issue 1 (4th February 2014) - Manlove, Jennifer; Welti, Kate; Wildsmith, Elizabeth; Barry, Megan
<x xml:space="preserve">Abstract</x> CONTEXT Although expanding research has found that relationship characteristics can shape contraceptive use among young adults, limited research has examined how relationship characteristics intersect to form distinct types of relationships and how relationship types are linked to contraceptive use. METHODS Data from the 2002–2005 rounds of the National Longitudinal Survey of Youth 1997 cohort were used to examine contraceptive use in 3, 485 young adult dating relationships. Latent class analysis was employed to develop a typology of relationships using measures of relationship structure (duration) and quality (intimacy, commitment and conflict). Multinomial logistic regression analyses were used to estimate associations between relationship type and contraceptive use and method choice at last sex. RESULTS Four types of relationships were identified, two shorter term and two longer term, differentiated by levels of intimacy, commitment and conflict. Young adults in longer term relationships with greater conflict and lower intimacy and commitment were less likely than those in other long‐term relationships to use hormonal and dual methods versus no method (relative risk ratios, 0.6–0.7). Hormonal method use, versus no method use or condom use, was more prevalent in short‐term relationships with greater intimacy and commitment and lower conflict than in other short‐term relationships (1.7 and 1.9, respectively). CONCLUSIONS Classifying short‐term relationships as "casual" or long‐term ones as "serious" may ignore heterogeneity within these categories that may have implications for contraceptive use. Future qualitative research could provide a better understanding of relationship types and couples' fertility intentions and access to and use of contraceptives.